Henry III: The Rise to Power and Personal Rule, 1207-1258. By David Carpenter. New Haven: Yale University Press, 2020. ISBN 978-0-300-23835-8. xxv + 763 pp. £30. Issue 2 (2021) - Wild, Benjamin Linley
No abstract available